FINANCIAL PERFORMANCE ANALYSIS OF TRANSPORTATION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2021-2023 - Waddah, Atik; Sam, Iskandar; Lutfi, Lutfi (Faculty of Economics and Business Universitas Jambi, 2026)
This study aims to analyze the financial performance of transportation companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The analysis focuses on evaluating company performance using profitability and activity ratios, including Net Profit Margin, Return on Equity, Return on Assets, Gross Profit Margin, and Total Assets Turnover. This research employs a quantitative descriptive approach using secondary data obtained from audited annual financial statements. The research sample consists of six transportation companies selected through purposive sampling based on data availability and listing consistency during the observation period. The results show that the financial performance of transportation companies varies significantly among firms. Several companies demonstrate relatively better profitability and asset utilization, indicating effective cost control and operational efficiency, while others exhibit lower performance due to inefficiencies in managing costs and assets. This study provides a clear assessment of the financial health and operational efficiency of Indonesian transportation companies from 2021 to 2023. It also offers practical guidance to help managers improve cost control and assist investors in making well-informed decisions.